Musica naturalis: Speculative Music Theory and Poetics, from Saint Augustine to the Late Middle Ages in France - Jeserich, Philipp (Baltimore, MD John Hopkins University Press, 2013)
Musica Naturalis delivers the first systematic account of speculative music theory as a discursive horizon for literary poetics. The title refers to the late medieval French poet Eustache Deschamps, whose 1392 treatise on verse writing, L'Art de Dictier, famously casts verse as "natural music" in explicit distinction to song, which Deschamps defines as "artificial." Philipp Jeserich links the significance of the speculative branch of medieval musicology to literary theory and literary production, opening up a field of study that has been largely neglected. Beginning with Augustine and Boethius, he traces the discourse of speculative music theory to the late fifteenth century, giving attention to medieval Latin and vernacular sources. Ultimately, Jeserich calls for the conservatism of Deschampss poetics and develops a new perspective on the poetics and poetry of the Grands rhétoriqueurs.Given Jeserich's reliance on the intellectual inheritance of late medieval French poetics and poetry, this book will appeal to English-speaking specialists of Old and Middle French, as well as scholars of the French Renaissance. It will also interest English-language medievalists of several other disciplines: intellectual historians and specialists of English, as well as scholars of Italian and Iberian literature.
Keywords: Middle Ages (500-1400); Music theory; France